Public health response and medical management of internal contamination in past radiological or nuclear incidents: A narrative review. (May 2022) - Li, Chunsheng; Alves dos Reis, Arlene; Ansari, Armin; Bertelli, Luiz; Carr, Zhanat; Dainiak, Nicholas; Degteva, Marina; Efimov, Alexander; Kalinich, John; Kryuchkov, Victor; Kukhta, Boris; Kurihara, Osamu; et al.
Abstract: Following a radiological or nuclear emergency, workers, responders and the public may be internally contaminated with radionuclides. Screening, monitoring and assessing any internal contamination and providing necessary medical treatment, especially when a large number of individuals are involved, is challenging. Experience gained and lessons learned from the management of previous incidents would help to identify gaps in knowledge and capabilities on preparedness for and response to radiation emergencies. In this paper, eight large-scale and five workplace radiological and nuclear incidents are reviewed cross 14 technical areas, under the broader topics of emergency preparedness, emergency response and recovery processes. The review findings suggest that 1) new strategies, algorithms and technologies are explored for rapid screening of large populations; 2) exposure assessment and dose estimation in emergency response and dose reconstruction in recovery process are supported by complementary sources of information, including 'citizen science'; 3) surge capacity for monitoring and dose assessment is coordinated through national and international laboratory networks; 4) evidence-based guidelines for medical management and follow-up of internal contamination are urgently needed; 5) mechanisms for international and regional access to medical countermeasures are investigated and implemented; 6) long-term health and medical follow up programs are designed and justified; and 7) capabilities and capacity developed for emergency response are sustained through adequate resource allocation, routine non-emergency use of technical skills in regular exercises, training, and continuous improvement.